Results of adjunctive coronary endarterectomy in 548 patients - (:unkn) unknown (FORUM MULTIMEDIA PUBLISHING, LLC, 2008)
Coronary endarterectomy is a controversial procedure that plays a particular role in the treatment of coronary artery disease. We retrospectively investigated the results for 548 patients who underwent coronary endarterectomy as an adjunctive therapy for coronary artery bypass graft surgery during the period between 1996 and 2004. We assessed short-term outcomes and identified risk factors for adverse outcomes. Mean patient age was 67.9 +/- 9.3 years and mean angina class was 2.7 +/- 0.3. The mean number of distal anastomoses was 3.8 +/- 1.1 patients (73.4%) had single and 151 (27.6%) multiple coronary artery endarterectomies. Of the 151 patients who underwent multiple endarterectomies, 97 (17.7%) had endarterectomies in 2 coronary arteries, 40 (7.2%) in 3 coronary arteries, 11 (2%) in 4 coronary arteries, 2 (0.36%) in 5 coronary arteries, and 1 (0.18%) in 6 coronary arteries. Postoperative mortality was 6.2% (34 patients). The predictors for early mortality were recent myocardial infarction and left ventricular dysfunction. Our results suggest that adjunctive coronary endarterectomy can be accomplished with acceptable results but with higher mortality rates than ordinary coronary artery bypass grafting. Adjunctive coronary endarterectomy should be considered as a last option for the surgical treatment of diffuse coronary disease.
Keywords: ARTERY ENDARTERECTOMY; BEATING HEART; CELL THERAPY; RECONSTRUCTION; DISEASE